Clinical comparison of different cardiovascular risk scores for cardiovascular risk prediction in Indian patients - Salam, Azad Abdul; Unni, T. Govindan; Benjamin, Bino; K., Prasanna C.; Ravi, Manoj (International Journal of Research in Medical Sciences, 2019)
Background: Cardiovascular diseases (CVD) are the main cause of mortality and disability in India. Early and sustained exposure to behavioral risk factors leads to development of CVD. The present study was conducted to compare different cardiovascular calculators for CVD risk assessment models in young Indian patients presenting with myocardial infarction. Methods: This study included 85 patients with myocardial infarction (MI). Their predicted 10-year risk of CVD was calculated using three clinically most relevant risk assessment models viz. Framingham Risk score (RiskFRS), American College of Cardiology/American Heart Association (RiskACC/AHA) and the 3rd Joint British Societies risk calculator (RiskJBS). Results: RiskFRS recognized the highest number of patients (15.4%) at high CVD risk while RiskACC/AHA and RiskJBS calculators provided inferior risk assessment but statistically significant relationship. RiskFRS and RiskACC/AHA (Pearson’s r 0.870, p<0.001). Conclusions: RiskFRS seems to be as most useful CVD risk assessment model in young Indian patients. RiskFRS is likely to identify the number of patients at ‘high-risk’ as compared to RiskJBS and RiskACC/AHA.